Pengaruh Sistem Pengendalian Internal, Partisipasi Masyarakat dan Transparansi Terhadap Efisiensi Anggaran Dana Desa pada Kecamatan Sungai Apit - Safitri, Nelly; Dwitayanti, Yevi; Hasibuan, Rahmawaty (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of the Internal Control System, Community Participation, and Transparency on Village Fund Budget Efficiency—both individually and simultaneously—in Sungai Apit District, Siak Regency, Riau Province. A quantitative approach was employed, utilizing primary data collected via questionnaires. The study population comprised 14 villages, with a sample of 42 respondents selected through purposive sampling, including Village Heads, Village Secretaries, and Financial Officers/Treasurers. Data were analyzed using multiple linear regression with the aid of IBM SPSS Statistics. The results indicate that the Internal Control System did not significantly affect Village Fund Budget Efficiency (β = −0.051; t = −0.147; p = 0.884). Similarly, Community Participation did not have a significant effect at the 5% level (β = 0.387; t = 1.829; p = 0.075), although it showed a tendency toward a positive influence at the 10% level. Transparency also showed no significant effect (β = −0.073; t = −0.207; p = 0.837). However, when considered simultaneously, the three variables significantly influenced Village Fund Budget Efficiency (F = 3.891; p = 0.016) and explained 23.5% of the variation in budget efficiency (R² = 0.235). These findings suggest that budget efficiency is more meaningfully influenced by the combination of internal control, community participation, and transparency.